Avaliação automática de versões oculares baseada em imagens - PINHEIRO, Jullyana Fialho (2018)
The version exam is a test performed by specialists in ophthalmology to detect restrictions, paralysis and disproportionate actions on the eye muscles in binocular movements, that is, the simultaneous movement of the eyes. This test is commonly used in the detection, followup and surgical planning of patients with strabismus. Strabismus is a condition where the eyes do not have adequate alignment, generating several problems not only of vision, but also social problems. This condition reaches approximately 4 % of the world population. Thus, the present work aims to present an automatic method developed to perform the version examination through face images. The proposed method is organized in seven steps: (1) image acquisition, (2) preprocessing, (3) eye location, (4) sclera segmentation, (5) iris location, (6) location of eyes corner and (7) measure of the version. The automatic measurement presented by the method was evaluated by the mean of the difference between the results provided by the method and the original versions measured by the specialist. As far as the version was concerned, the proposed method obtained mean accuracy and error, respectively, of 85.18 % and 0.29 for the Medial Rectus muscle, 100 % and 0 for the Lateral Rectus muscle, 86.9 % and 0.47 for the Inferior Oblique muscle, 87.5 % and 0.16 for the Superior Rectus muscle, 100 % and 0 for the Superior Oblique muscle, and 95.23 % and 0.28 for the Inferior Rectus muscle.